Analysis University of Surakarta KIP Scholarship Recipients Using the Fuzzy MADM Method and C-45 - Sudalyo, Ramadhian Agus Triono; Mukti, Bayu (Sinkron : jurnal dan penelitian teknik informatika, 2021)
The impact of the Covid-19 pandemic has forced the economic activity of the Indonesian population to decline drastically, which has an impact on the education funding process. Given these problems, it is necessary to develop a Decision-Making System to assist the selection process for KIP admissions for students who meet the requirements. The purpose of this research is that the provision of KIP can be right on target. For decision making, three stages are used with the method used, the first stage is the C-45 method for student priority decision making, the second stage is the Fuzzy MADM method, and the third stage is ranking according to the total quota. which is determined. The initial selection used the C-45 method with the variables of GPA, parents' income, achievements, parental dependents, and cases. The results of the C4.5 calculation show that the first priority is parental dependents with a Gain value of 0.007822696, followed by a GPA with a Gain value of -0.130011482, the third priority is Parents' Income with a Gain value of -0.702657067 and the last priority is an achievement. The results of the calculation are continued with Fuzzy MADM resulting in 5 rules used to determine student priorities (can) or not. The results achieved from 140 students who applied were accepted by 135 students who passed the initial stage, and out of 135 rankings, 70 students were determined to receive scholarships from the Government with the highest calculation score of 21 and the lowest of 14.4.